Pandemic imposed remote work arrangements and resultant work-life integration, future of work and role of leaders: A qualitative study of indian millennial workers - Debashish Sengupta; Dwa Al-Khalifa (Administrative Sciences, 2022)
The unprecedented nature and scale of the COVID-19 pandemic resulted in mass lockdowns around the world, and millions of people were forced to work remotely for months, confined in their homes. Our study was aimed at understanding how pandemic-imposed remote work arrangements affected millennial workers in India. With signs of the pandemic slowing down, but with the likelihood of organizations retaining some of these work arrangements, the paper also explores how these are likely to affect the future of work, and the role that organizations and leaders have in managing the workforce in the 'new normal'. The study follows an interpretivist paradigm and qualitative research approach using the narrative method as a key research strategy. The data was collected using in-depth interviews from Indian millennial respondents employed in both private and government sectors. The findings show a kind of work-life integration for the workers as a result of the pandemic-imposed remote work arrangements. This integration has been caused by four different types of issues that have also emerged as four major themes which have resulted in a further 10 sub-themes. The four major themes identified in this research are Managerial Issues, Work Issues, Logistical Issues, and Psychological Issues.
Keywords: 350; COVID-19; mandatory work from home (MWFH); narrative inquiry; pandemic; remote work arrangements; work-life integration